The media contest during the Iran–Iraq war: The failure of mediatized Shiʿism. (September 2022) - Kalantari, Mohammad R
This article explains why Iran was unsuccessful in its efforts to persuade Shiʿi Iraqis to support Iran during the critical early years of the Iran–Iraq war. Analysis of Iranian and Iraqi framing communicated to that target population shows Iran failed due to both structural and cultural factors. Its media strategy lacked reach and variety and it misunderstood the cultural identity of Shiʿi Iraqis. The author makes use of original archive material of radio transcripts from 1981–1983 as well as other primary sources and historical accounts. The research makes an original theoretical contribution by applying media contest theory to a military confrontation between two sovereign states, rather than between a state 'authority' facing a non-state 'challenger'. The findings have implications for considering how Iran today may communicate more effectively beyond its borders through regional media strategies and thus the viability of a mediatized Shiʿism.